2012
DOI: 10.1136/heartjnl-2012-301682
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac disease and cognitive impairment: a systematic review

Abstract: Cognitive impairment in cardiac patients may interfere with disease management. This review describes studies examining specific cognitive impairments in cardiac patients and studies that investigate the link between echocardiographic and cognitive measures. Executive function impairments were frequently reported in different patient groups. Also, lower cardiac output and worse left ventricular diastolic function are linked to executive function deficits. In cardiac patients, special attention should be paid t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
108
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(125 citation statements)
references
References 58 publications
6
108
0
9
Order By: Relevance
“…Subclinical left ventricular (LV) dysfunction has also been associated with early cognitive impairment; however, findings are inconsistent. While some studies have shown associations between impaired cognition and LV systolic dysfunction,2, 3 one investigation found stronger relationships with LV diastolic dysfunction 4…”
Section: Introductionmentioning
confidence: 96%
“…Subclinical left ventricular (LV) dysfunction has also been associated with early cognitive impairment; however, findings are inconsistent. While some studies have shown associations between impaired cognition and LV systolic dysfunction,2, 3 one investigation found stronger relationships with LV diastolic dysfunction 4…”
Section: Introductionmentioning
confidence: 96%
“…We hypothesized that GLS would relate to cognition, especially memory13, 14 and executive function,15, 16 known to be most affected by compromised cardiovascular function. We also hypothesized that GLS would have stronger associations with cognition than LVEF.…”
mentioning
confidence: 99%
“…«немых»), а также возникновение микрогеморрагий на фоне приема антикоагулянтов. При этом на-до принимать во внимание и сопутствующую сердечно-сосудистую патологию у больных с ФП: артериальную гипертонию, атеросклероз аорты и брахиоцефальных артерий, СД [36]. Вклад данных факторов как причины когни-тивных нарушений у больных с ФП подтвер-ждается прямой зависимостью деменции от количества баллов по шкале CHA 2 DS 2 -VASc [34,35].…”
Section: Discussionunclassified